Should predictive scores based on vital signs be used in the same way as those based on laboratory data? A hypothesis generating retrospective evaluation of in-hospital mortality by four different scoring systems. (May 2016) - Kellett, John; Murray, Alan
Abstract: Background: few studies have compared the discrimination of predictive scores of in-hospital mortality that used vital signs with those using laboratory results in different patient populations. Methods: a hypothesis generating retrospective observational cohort study. A score that only used vital signs was compared with three other scores that used laboratory changes in 44, 985 medical and 20, 432 surgical patients. Results: the discrimination of the score based only on vital signs was highest for the prediction of in-hospital death within 24 h. In contrast the, albeit lower, discrimination of scores based only on laboratory data remained constant for the prediction of death up to 30 days after hospital admission. Moreover, the discrimination of scores based only on laboratory data was higher in surgical than in medical patients. Conclusion: in acutely ill medical patients a vital sign based score appears to predict mortality within 24 h better than scores using laboratory data. This may be because in acutely ill patients vital sign changes indicate how well a patient is responding to a current insult. In contrast, for patients without acute illness laboratory data may be a more valuable indication of the patient's capacity to respond to insults in the future.